2020
DOI: 10.21521/mw.6427
|View full text |Cite
|
Sign up to set email alerts
|

Transition period and subclinical ketosis in dairy cattle: association with milk production, metabolic and reproductive disorders and economic aspects

Abstract: Many dairy cows experience a high incidence of health problems during the transition period (TP). The TP is an intermediate stage of various digestive, metabolic and reproductive functions which determine the general health status at the time of calving and during the first weeks postpartum. Negative energy balance due to increased energy demand at parturition and significantly reduced dry matter intake relative to demand is an important determinant. Consequently, substantial lipid mobilization from adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
(221 reference statements)
0
18
0
Order By: Relevance
“…Some metabolic diseases are often seen in HYDC related to energy metabolism (Drackley, 1999), significant increase of the proportion of HYDC in lactating dairy cows population in Turkey in the last 28 years will probably brought related metabolic and reproductive disorders, which might be a reason for the increasing culling rate in the last 3 years. The last 3 weeks of pregnancy and the first 3 weeks of the post-partum period is known as transition period (Deniz et al 2020, Drackley 1999Grummer 1995). According to Bell (1995), cows producing 30 kg milk daily need 2 times more amino acids, 4.5 times more fatty acids, and 2.7 times more glucose for lactation on day 4 post-calving than on day 4 pre-calving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some metabolic diseases are often seen in HYDC related to energy metabolism (Drackley, 1999), significant increase of the proportion of HYDC in lactating dairy cows population in Turkey in the last 28 years will probably brought related metabolic and reproductive disorders, which might be a reason for the increasing culling rate in the last 3 years. The last 3 weeks of pregnancy and the first 3 weeks of the post-partum period is known as transition period (Deniz et al 2020, Drackley 1999Grummer 1995). According to Bell (1995), cows producing 30 kg milk daily need 2 times more amino acids, 4.5 times more fatty acids, and 2.7 times more glucose for lactation on day 4 post-calving than on day 4 pre-calving.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bell (1995), cows producing 30 kg milk daily need 2 times more amino acids, 4.5 times more fatty acids, and 2.7 times more glucose for lactation on day 4 post-calving than on day 4 pre-calving. This is a huge change and requirement for the metabolism of HYDC, which might result in NEB and associated postpartum metabolic and reproductive diseases (Deniz et al 2020). Metabolic and reproductive diseases frequently encountered in the peripartum period in 61 herds in HYDCs are listed as follows: 7.2% milk fever (0-44.1%), 9% retained placenta (0-22.9%), 3.3% abomasum displacement (0-14%), 3.7% ketosis (0-20%), metritis 12.8% (0-66%), 13.5% cystic ovaries (0-58.8%) and 12.8% uterine infections (0-66%).…”
Section: Discussionmentioning
confidence: 99%
“…Dairy cows must orchestrate the metabolic challenges during the transition from dry-period to early lactation to support milk production with an adequate glucose supply. These critical production stages can result in several postpartum (PP) metabolic disorders if dairy cows do not overcome negative energy balance (NEB) due to reduced dry matter intake and other complications (Baumgard et al 2017, Overton et al 2017, Deniz et al 2020. NEB is the main reason during the transition period and can negatively affect milk production due to subclinical ketosis (SCK) (Dohoo and Martin 1984;McArt et al 2012), metabolic and reproduction parameters (Whitaker et al 1983; Uyarlar et al 2018;Deniz et al 2020) and farm pro tability through decreased milk production and increased risk of metabolic diseases (McArt et al 2015;Raboisson et al 2015;Benedet et al 2019;Deniz et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Beta-hydroxybutyric acid concentration (BAC) in the blood (BBAC) or milk (MBAC) is one of the most tested ketone bodies among others as such acetone and acetoacetic acid in recent years (Suthar et Santschi et al 2016) indicate the NEB, that can result in clinical ketosis (CK) and SCK in early lactation. Thus, HK became an economically relevant postpartum metabolic problem in terms of its impact on farm pro tability, especially in Holstein dairy farming (McArt et al 2015;Raboisson et al 2015;Mostert et al 2017;Deniz et al 2020), however, there are not enough papers published about Montbeliard, Simmental and Holstein-Crossbred. Various studies in Holstein revealed a prevalence of 21.8% (Suthar et al 2013) and 24% (Brunner et al 2019) worldwide if tested in the blood, in which a cut-off level for BBAC ≥ 1.2 mmol/L was taken.…”
Section: Introductionmentioning
confidence: 99%
“…Subclinical ketosis is defined as a disease in which the concentration of ketone bodies in the blood of postpartum cows increases without clinical signs. After ketosis occurs in dairy cows, a large amount of fat and protein are mobilised to provide adequate nutrition (Deniz et al, 2020). GH also stimulates the breakdown of fat to produce glucose, and GH has long-term effects.…”
mentioning
confidence: 99%